Cultural Sedimentations - Ethnography on the Materiality and Historicity of Aesthetic Practices - Engel, Juliane; Beach, Dennis; Jörissen, Benjamin (Routledge, 2020)
The importance of materiality in learning and education processes has been emphasized in numerous empirical studies and theoretical argumentation figures, dating from both before and after the material turn. Therefore, it is evident to take the dimensions of material characteristics, structures and properties, cultural historical inscriptions as well as modern design processes, and spatial arrangements (e.g. architectures and environments) into account. As most objects and material surroundings of our everyday life have been conceived for a special use, we have to deal with their pre-designed structures and their historical dimensions. Even if we alienate them from their original purpose, the cultural sedimentations leave (in-)visible traces in our (aesthetic) practices as well as our practices deposit new sediments. But of course, materialities of education need to be discussed in the context of global(ising) capitalism, education justice and equity through ethnographies of education experiences. Therefore, (meta-)ethnographies on race, space and class history will take place in our discussions. Against this background, we focus on the historicity of materiality and relational practices and how both may influence, produce and generate each other. In this context we question how the historicity of materiality articulates itself in relational practices and how people experience the historicity inscribed into the material form for instance of images, poems, performances and buildings. By asking questions like these we strive to open up two mainly theoretical (Section 1), two methodological (Section 2) and five mainly empirical approaches (Section 3) towards aesthetic practices as relational education processes (see Table of Contents). The ethnographies are situated in arts and museum education, school, post-digital and youth culture, studies of design and new maker culture.
Keywords: aesthetics; aesthetic education; aesthetic practice; materiality; material turn; ethnography; qualitative research; education